An Analysis of the Influence Using Online Games: Wordwall in Improving Student’s Reading Skill in X Grade at Kartikatama Metro High School - Fikri , Arief Hadziq; Mufidah, Aqlin Naila Rosydatul (ENJEL: English Journal of Education and Literature, 2025)
This article aims to provide a further understanding of the utilization and influence obtained from web-based online games using Wordwall media which is considered the influence in improving the reading ability of grade X students at SMAN Kartikatama Metro. Qualitative descriptive is an analysis involves the processing of survey data that assesses the relationship between the use of Wordwall and student ability which is a factor in student reading comprehension learning outcomes. The subject of this research is from class X students at Kartikatama Metro High School which amounted to 20 students. Data were obtained from multiple-choice questions pre-test and post-test. The analysis used in this study is descriptive statistics. The study results show that the average pre-test scores of class X students are 63.50, while the average score of the post-test is 81. The percentage of pre-test results shows that around 95% are included in the fewer categories and 1% is in the sufficient category. The percentage of post-test results showed an increase of 25% in the good category and 15% in the very good category. There are 50% of the total students who have improved their reading ability. The conclusion of this research is that there is a positive influence by using online game Wordwall on the reading ability of grade X students at Karkatama Metro High School.